Plasmonic coupling-dependent SERS of gold nanoparticles anchored on methylated DNA and detection of global DNA methylation in SERS-based platforms. (23rd October 2015) - Nguyen, Anh H; Lee, Jong Uk; Sim, Sang Jun
Abstract: Global DNA methylation is in the spotlight as a treatment and diagnostic strategy for several severe diseases. However, conventional methods entail laborious work, high costs, and high concentrations at a nanomolar range. We developed a new method based on surface-enhanced Raman spectroscopy (SERS) to detect global DNA methylation. This was chosen due to the following two reasons: (i) genomic DNA has many neighbouring methylcytosine (mCpG) sites in CpG islands, and (ii) anti-mCpG immunogold colloids are coupled to amplify plasmon coupling and then enhance SERS intensity when they bind to the mCpG sites on the genome. We first used a DNA backbone with well-defined distances between different mCpG sites to study the link between plasmon coupling and a SERS signal as a basis for plasmonic coupling-dependent SERS. The plasmon shift and SERS enhancement were monitored by plasmon coupling with different mCpG spacing on a genomic DNA backbone. Global DNA methylation was then detected via SERS in a coupled gold nanoparticle–silver nanowire (AgNW) and a simple glass-based system on a multi-channel chamber. DNA samples were simply absorbed onto a cetyltrimethylammonium bromide (CTAB)-positive-charge AgNW surface and a microscopic glass, and immunogold colloids were then used to detect the methylation status by recognizing mCpG sites. The detection limits for global methylated DNA on the platform of glass and the silver nanowire were 195 fg ml −1 and 18 fg ml −1, respectively. Moreover, the approach of aligning gold nanoparticles on methylated DNA could be applied for biomolecular templates that can assemble themselves, and a proportional correlation between the concentration and SERS intensity could allow for a quantitative assay of DNA methylation from various samples.